The real Joan of Arc - Wooster, Nora, 1906- (Sussex : The Book Guild Ltd, 1992)
Origin of Jehanne - The introduction to the French Court - Oppositioon - Liberation of Orleans - Rheims and the coronation - Eclipse and capture - Captivity - Interogations - Trial and Abjaration - Relapse and execution
Keywords: Joan of Arc, -- Saint, -- 1412-1431.